Effects of Different Concentrations of Sucrose on Vase Life of Rose (Rosa sps.cv. Dutch Hybrid) - Chaudhary, G.; Khanal, A. (Journal of the Institute of Agriculture and Animal Science, 2018)
Keeping quality is an important parameter for evaluation of rose cut flower quality, both in export and domestic markets as fresh cut rose flowers are highly perishable due to limited water uptake and low available energy. Carbohydrate is the main food source to maintain the energy requirement for flowers .An experiment was conducted at Horticulture Laboratory of Institute of Agriculture and Animal Science, Lamjung, Nepal on January 2017 in order to find out best concentration of sucrose that enhances and prolongs the better flower quality and longevity. Experiment was laid out with 10 treatments viz. tap water, tap water + 2% sucrose, tap water + 4% sucrose, tap water + 6% sucrose, tap water + 8% sucrose, distilled water, distilled water + 2% sucrose, distilled water + 4% sucrose, distilled water + 6% sucrose and distilled water + 8% sucrose under completely randomized design with three replications. Rose sticks were harvested at flower bud stage and two sticks were kept in each vase solution. Effect of different concentrations of sucrose solution on water uptake, weight gain or loss, neck bending, flower diameter, days to full bloom and vase life was affected significantly. The rose flower held in distilled water + 6% Sucrose was recorded to have higher value (7.77cm) for flower diameter at 10 days followed by Tap water + 6% Sucrose with value 7.62cm. Similarly, lower flower diameter (2.29cm) was observed in Tap water at Day16 followed by Distilled water with value 3.21cm. Similar pattern was observed in all other parameters having highest vase life (19.5 days) in Distilled water + 6% Sucrose and lowest (15.17 days) in tap water only. Among different concentrations of sucrose solution, distilled water + 6% sucrose was found highly effective for longevity of cultivar.